1981
DOI: 10.1017/s0031182000080549
|View full text |Cite
|
Sign up to set email alerts
|

Cercaria vaullegeardi Pelseneer, 1906 (Digenea: Hemiuridae); development and ultrastructure

Abstract: SUMMARYCercaria vaullegeardi develops in daughter sporocysts within the digestive gland of the prosobranch Gibbula umbilicalis. On emergence into the host mantle cavity the cercarial body retracts into the cystophorous tail, the ‘encysted’ cercaria being then shed into the sea. The encysted cercaria is described at the ultrastructural level for the first time and developmental stages are redescribed. The cercarial body has no penetration or cystogenous glands: a single type of sub-tegumental secretory cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Two further instances of homoplasy are seen in bivesiculids (Pearson, 1968), and in azygiids (Odening, 1976, fig. 10, p. 74) and hemiurids (Cable, 1963;Matthews, 1981Matthews, , 1982, all of which have terminal primary excretory pores; that is, character 43, in anterior half of tail, does not apply to Brooks' conglomerate hemiuriforms. The Haploporiformes are said to have character 43, in anterior half of tail, in fig.…”
Section: Cercariamentioning
confidence: 99%
“…Two further instances of homoplasy are seen in bivesiculids (Pearson, 1968), and in azygiids (Odening, 1976, fig. 10, p. 74) and hemiurids (Cable, 1963;Matthews, 1981Matthews, , 1982, all of which have terminal primary excretory pores; that is, character 43, in anterior half of tail, does not apply to Brooks' conglomerate hemiuriforms. The Haploporiformes are said to have character 43, in anterior half of tail, in fig.…”
Section: Cercariamentioning
confidence: 99%
“…The embryonic development was shown by Pelseneer (1906) for C. vaullegeardi and by Matthews (1981a) for the cercaria of L. furcolabiatum. The most striking differences between the early stages of the two cercarial species are the shape of the caudal cysts and the location of the excretory appendages.…”
Section: Discussionmentioning
confidence: 91%
“…"Cercaria oaullegeardi" described by Matthews (1980Matthews ( , 1981a from G. umbilicalis (Table 1) was shown in an electrophoretic study by Gibson et al (1985) to be identical with L. furcolabiatum. These authors found that L. furcolabiatum from rockling and conger eels can be distinguished from L. rufoviride from eels.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations